Contextualizing the Onset of the Great Ordovician Biodiversification Event. (25th March 2018) - Harper, David A.T.; Servais, Thomas
Abstract : We introduce and briefly summarize a collection of papers contextualizing the onset of the Great Ordovician Biodiversification Event, initiated during the first meeting of IGCP project 653 at Van Mildert College, Durham University, UK, in September 2016.